Latin inscription on Chancel steps - Ghosh, Ayan (2023)
In recognition of Reverend William Kew Fletcher's services towards the restoration of St. Thomas Church, his friends laid down a memorial in the form of Latin inscriptions on the steps leading to the Chancel. The inscriptions mention his name, ecclesiastical rank (arch chaplain), and Roman numerals of the year, MDCCCLXXI (1871), in which it was inscribed.